Women in decision-making : panorma of activities in the framework of the third medium-term community action programme on equal opportunities for women and men (1991-95) (Employment & social affairs, 1997)
This report gives an overview and an evaluation of the activities of the European Expert Network "Women in Decision-Making" during the period 1992-96. The goal of this report is twofold. Firstly, it describes the activities of the Network and summarizes their results. It then analyses the various working tools, examines the problems encountered and draws up the consequences of the Network's activities at the European and national level. Secondly, the report aims to form a working tool for the future, examines the perspectives and formulates some recommendations for further action.